DIPLOMASI EKONOMI INDONESIA DALAM KETENTUAN WORLD TRADE ORGANIZATION - Argo Dewantara; Setyasih Harini, GPH. Dipokusumo (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2017)
DIPLOMASI EKONOMI INDONESIA DALAM KETENTUAN WORLD TRADE ORGANIZATION(Studi Kasus Perdagangan Impor Beras Dari Vietnam Era Presiden Susilo Bambang Yudhoyono)Argo Dewantara,Setyasih Harini, S.IP., M.Si., Drs. GPH. Dipokusumo, M.Si.ABSTRACT This thesis is aimed to discuss the economic diplomacy constituting the economic instrument in achieving the national interest. To maintain the national food tenacity in which at that time there was a lack of national rice stock during Susilo Bambang Yudhoyono reign, Indonesia imported rice from Vietnam to meet the need for food stock, recalling Vietnam’s good agricultural condition. The agreement o f rice importing between these two countries is governed by the agreement in WTO agricultural sector through Agreement of Agricultural (AOA) existing in the rules of market access, domestic subsidy, and import subsidy with those regulations thereby generating the provision of rule specified in the agreement and creating a fair non-discriminative trade between WTO members. It is the requirement with which the members of WTO should comply. Using Economic Diplomacy and International Organization theories, the method used in this research was qualitative one with secondary data, technique of collecting secondary data and document-based research, and library research through descriptive elaboration. Through Indonesian Economic Diplomacy, according to WTO’s provision, the author found Indonesian Economic Diplomacy needed support and good coordination and shared objective of government, private, stakeholders, and the optimization of economic diplomacy on (central and local) government’s capacity and domestic ability and could make Indonesian economic diplomacy in WTO organization change any time; therefore Indonesian economic diplomacy could run well in WTO issues and made Indonesian economic diplomacy the symbol of state’s power in international view. Keywords: Economic Diplomacy, World Trade Organization (WTO), Agreement of Agriculture (AOA).